Periacetabular triple osteotomy by single anterior approach for children under 6-years-old with severe acetabular deficiency: prevention of retroversion and anterior impingement. Issue 6 (November 2021) - Najdi, Hassan; Mouarbes, Danny; Karnib, Soha; Dimassi, Ahmad
Abstract : The aim of this study was to perform periacetabular triple osteotomy (PATO) in children under 6-years-old with severe acetabular deficiency aiming to obtain important correction and avoid excessive pressure on epiphysis, anterior overcorrection and acetabular retroversion. This is a retrospective study of 29 PATO using single anterior approach in 24 patients under 6-years-old with dysplasia of the hip. Clinical examination and radiographic evaluation were done pre-op, post-op and at last follow-up. Computed tomography (CT) scan was obtained, comparing operated hip to contro-lateral normal hip. Clinical examination of the operated hip, at the last follow-up, showed a normal range of motion with nonsignificant difference when compared to normal hip. All hips were classified as Wicart A, and all activities were allowed. Radiographically, X-ray revealed improvement of all parameters postoperatively, with nonsignificant change compared to the last follow-up. CT-2D axial analysis demonstrated the absence of acetabular retroversion with good anterior and posterior coverage. CT-3D imaging comparing the anterior acetabular inclination, anterolateral and posterolateral inclination angles of operated hip and normal hip showed comparable results. Patients less than 6 years with severe acetabular deficiency could benefit from PATO. Performing osteotomies close to joint gave important acetabular fragment freedom, allowing an important correction. Appropriate manoeuver of reorientation avoided anterior overcorrection and acetabular retroversion, responsible for early pain and osteoarthritis. Age should not be the only criteria to choose the type of osteotomy. Level of evidence: level IV.